(untitled) (Nordic Journal of African Studies, 2000)
In the end, we are judged, Condemned, classified, determined in our undertakings, destined to a certain mode of living or dying, as a function of the true discourses which are the bearers of the specific effects of power (Foucault 1980: 94). On the grey bank of the Joliba, dotted with the shells of giant oysters, women were drawing water in great gourds. Slaves were being driven along in single file by an overseer. Everyone carefully avoided looking at the priest, for it was never wise to get in the way of a master of Komo. You never knew when he might be angry and unleash the forces that brought barrenness, violent death or epidemics. So Koumare met only with lowered eyelids, closed eyes, attitudes of furtiveness and fear. (Condé 1988: 42–43)